2002
DOI: 10.1097/00000637-200206000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of Color Doppler Sonography for Assessing Hemodynamics of Free Flaps for Head and Neck Reconstruction

Abstract: This report focuses on the monitoring of intraoperative and postoperative hemodynamics of free flaps for repair of head and neck defects by color Doppler sonography (CDS). The study group included 20 patients with head and neck cancer who underwent resection and reconstruction with free flaps. The hemodynamics in the feeding arteries of the flaps were measured during the following six stages: before surgery, immediately after microvascular anastomosis, and on postoperative days 1, 3, 5, and 7. The pulsatility … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
23
0
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 19 publications
4
23
0
2
Order By: Relevance
“…165 Smit et al demonstrated that an implantable Doppler device increased salvage rates compared with clinical monitoring alone, but this did not reach statistical significance (Level III Evidence). 166 Advocates of color Doppler ultrasonography cite its ability to provide accurate assessment of patency through vessel flow and velocity approaching 100 percent negative and positive predictive [167][168][169] Monitoring is possible in buried bone and muscle free flaps. [180][181][182] Drawbacks are that the color Doppler devices are expensive and require expertise.…”
Section: Postoperative Monitoringmentioning
confidence: 99%
See 1 more Smart Citation
“…165 Smit et al demonstrated that an implantable Doppler device increased salvage rates compared with clinical monitoring alone, but this did not reach statistical significance (Level III Evidence). 166 Advocates of color Doppler ultrasonography cite its ability to provide accurate assessment of patency through vessel flow and velocity approaching 100 percent negative and positive predictive [167][168][169] Monitoring is possible in buried bone and muscle free flaps. [180][181][182] Drawbacks are that the color Doppler devices are expensive and require expertise.…”
Section: Postoperative Monitoringmentioning
confidence: 99%
“…19 Through multicenter cooperatives, enough power can be obtained to prove practices to payers, patients, and the scientific community. [167][168][169] Expensive and requires expertise; reading by radiologist limits monitoring to once every few days Near-infrared spectroscopy~1 00% 170-172~1 00% [170][171][172] Dislocation of flap probe influences measurement considerably; value trends are more important than absolute values; Sto 2 ≤30% or a drop ≥20% per hr sustained more than 30 min is predictive of flap failure 173 PPV, positive predictive value; NPV, negative predictive value; Sto 2 , tissue oxygen saturation.…”
Section: Postoperative Monitoringmentioning
confidence: 99%
“…[32][33][34][35][36][37] Its strength is the precise and quantitative characterization of inflow and outflow, 38 and it has been reported to pre- 35 The technique, however, requires experience with the device, as well as detailed knowledge of the recipient site and flap. This means that in some cases the radiologist and microsurgeon both have to be available when assessing the flap.…”
Section: Color Duplex Sonographymentioning
confidence: 99%
“…33 This explains why in several reports the system is often used no more than once a day. 34,35,37,38 Color duplex sonography has also been used as complementary test in studies addressing near-infrared spectroscopy 39,40 or the implantable Doppler system. 29 Two studies, with a combined population of 65 cases of head and neck reconstructions and buried flaps, reported the positive and negative predictive values of 100 percent.…”
Section: Color Duplex Sonographymentioning
confidence: 99%
“…by an implantable Doppler system [31], by color duplex sonography [32][33][34][35][36][37] near-infrared spectroscopy [38,39], microdialysis [40][41][42], and laser Doppler flow metry [43]. Indocyanine green (ICG) angiography has been used in the evaluation of flap perfusion and is now in the clinical testing phase although costs for this method are fairly high [44][45][46].…”
Section: Discussionmentioning
confidence: 99%